Rooting Mediates the Effect of Stress by Acculturation on the Psychological Well-Being of Immigrants Living in Chile - Vera-Villarroel, P (Public Library of Science, 2019)
Migration is a social phenomenon that has an impact both on the lives of the people who migrate, and on the societies who receive them; with psychological well-being being one of the most affected variables. The objective of this research is to analyze the possible mediating role of rooting in the host location on the negative effect that acculturation stress has on the level of well-being. Data for this study were collected using 699 Colombian and Peruvian immigrants who have been permanently residing in Chile for more than six months. Participants were assessed by using Riff’s Psychological Well-being Scale, rooting of Torrente et al., and Ruiz et al. scales of stress. The results demonstrated the mediating role of settling down within the host country in relation to stress and psychological well-being, except for the sub-dimension of autonomy. It is concluded that the need for rooting in the host country is a protective factor against the negative effects of stress on perceived well-being. © 2019 Urzúa et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.